Teacher-centered professional development - Díaz-Maggioli, Gabriel, 1963- (Association for Supervision and Curriculum Development, 2004)
Teacher-Centered Professional Development is a hands-on guide to collaborative skill building for educators. It introduces the Teacher's Choice Framework, a model that empowers teachers by helping them choose and initiate professional growth activities according to their schedules, strengths, and needs. The book describes a wide variety of professional development strategies, including mentoring, journal writing, peer-to-peer coaching, and seminars. For each strategy, the author provides. A brief history of the research base. A step-by-step guide to implementing the strategy. Sample handouts an.